Strategic Analysis and Experiential Learning in Business Education: A Case Study of PT Eksonindo MPI - Nurjanah, Erni; Rahmawati, Lusiana; Sumirat, Irham; Maria Intan, Cyndy (Universitas Indo Global Mandiri Palembang, 2025)
Objective: This study aims to analyze the strategic position of PT Eksonindo Multi Product Industry (PT EMPI), a national manufacturing firm, while simultaneously exploring the pedagogical value of Project-Based Learning (PBL) in strategic management education. The research seeks to contribute empirical insights into how structured strategy models can be applied in real business contexts and translated into practical decision-making processes. Design/Methods/Approach: The research adopts a qualitative descriptive method using a case study approach. Data were collected from student projects involving interviews, company documents, and reflective journals, all structured according to Fred R. David’s three-stage model—input, matching, and decision. Strategic analysis tools used include IFE, EFE, Strategic Group Mapping (SGM), SWOT, SPACE, and QSPM. Findings: The results indicate that PT EMPI is in a favorable strategic position, supported by strong internal capabilities and attractive external opportunities. The company is best suited to adopt an aggressive growth strategy, with market penetration emerging as the most attractive option based on the QSPM analysis. The SGM illustrates the company’s position in a high-differentiation, mid-to-high price cluster, supporting its competitive orientation. Additionally, the use of real-world cases enhanced students’ ability to apply theory to practice, improving their analytical, collaborative, and reflective skills. Originality/Value: This study offers an integrative perspective by combining strategic analysis with experiential learning. It showcases how students can engage in applied strategy formulation through real business projects, contributing to both academic literature and teaching practices in management education. Practical/Policy implication: The findings provide valuable insights for SMEs on how to use structured strategy tools for decision-making and highlight the effectiveness of academic–industry collaboration. The research also demonstrates the practical value of integrating real cases into university curricula to build future-ready managerial skills. Keywords: Manufacturing industry case study, Project-Based Learning (student-centered), Strategic business, Strategic management